(untitled) (Dhaka University Journal of Biological Sciences, 2022)
Effects of zinc, vermicompost and their joint effects on growth, yield and nutrient accumulation in the leaves and bulb of onion (Allium cepa L.) were examined. The experiment was conducted in a completely randomized design (CRD) replicated thrice with twelve treatments involving different doses of Zn and vermicompost and a control treatments. Growth parameters viz. leaf height, leaf number, leaf area, leaf area index, bulb height, bulb area and fresh and dry weight of leaf, stem, bulb and root were assessed. The highest leaf height (63.87 cm), leaf number (28), leaf area (614.21 cm2), fresh weight (29.46 g) and dry weight (10.79 g) at first harvest were found in 30% vermicompost + 70% Zn application. The highest leaf height (42.33 cm), leaf number (15), leaf area (328.21 cm2), bulb height (5.67 cm), bulb equatorial diameter (5.67 cm), fresh weight (28.77 g) and dry weight (6.21 g) were found at second harvest in 30% vermicompost + 70% Zn. The maximum nitrogen, phosphorus, potassium and Sulphur content of leaf were observed in 80% vermicompost + 20% Zn application. The maximum nitrogen, phosphorus, potassium and sulphur content of bulb were observed in 60% vermicompost + 40% Zn application. The overall best growth performance and nutrient accumulation were observed in 30% vermicompost + 70% Zn application. Dhaka Univ. J. Biol. Sci. 31(1): 59-66, 2022 (January)